Descriptions monumentales et discours sur l'édification chez Paulin de Nole : le regard et la lumiè̀re (epist. 32 et carm. 27 et 28) - Herbert de la Portbarré-Viard, Gaë̈lle. (Vigiliae Christianae, Supplements, 2006)
Pontius Meropius Paulinus (ca 353-431), one of the greatest poets of Late Latin Poetry and author of an important correspondence, was born in a wealthy family of the Gallo-Roman aristocracy in Bordeaux. After his spectacular conversion to asceticism and his sacerdotal ordination, he set up definitively as a monk in Italy, in Campanian Nola besides the tomb of St. Felix. There, Paulinus devoted his considerable fortune to the restructuring of the monumental complex which has appeared around this holy place, since the early years of the fourth century and mainly a church. This book is a literary and spiritual study of the description of this complex (carm. 27 and 28 and epist. 32), an other way of edification (the edification of the soul in temple for her creator.) A careful comparison with archaeological testimonies must help estimate the status of Paulinus'monumental descriptions. *** Pontius Meropius Paulinus (vers 353-431), un des plus grands poètes de l'Antiquité tardive, auteur d'une importante correspondance, est issu d'une riche famille de l'aristocratie bordelaise. Après sa conversion spectaculaire à l'ascétisme et son ordination sacerdotale, il vint s'installer définitivement en tant que moine à Nole en Campanie auprès de la tombe de saint Félix. Là Paulin consacra sa fortune considérable à la restructuration du complexe monumental apparu autour de ce saint lieu, depuis les premières années du quatrième siècle, principalement une église. Ce livre est une étude littéraire et spirituelle de la description de ce complexe (carm. 27 et 28; epist. 32), une autre sorte d'édification (celle de l'âme en temple pour son créateur). Une comparaison prudente avec les témoignages archéologiques permettra d'évaluer le statut des descriptions monumentales de Paulin.